Konsep Pelaksanaan Wakaf Uang di Indonesia - St Samsuduha; Yush Nawir (Al-Tafaqquh: Journal of Islamic Law, 2022)
This paper examines the concept of implementing cash waqf in Indonesia. This writing study approach uses a theoretical study approach and interpretation of library materials. This study needs to be carried out to provide an understanding of the process of implementing cash waqf for the welfare of Muslims, and other people in general. Based on the results of the analysis, it is concluded that cash waqf is waqf in the form of funds handed over from assets in cash. This type of cash waqf also includes securities that can be managed by banks as LKS-PWU. Cash waqf is oriented towards productive investment that is lawful and does not conflict with Islamic law. The profits are then earmarked for the welfare of the beneficiaries. Cash waqf has only developed in recent years, previously people were more familiar with waqf of immovable property such as land. Currently, cash waqf has been legally protected in Indonesia so as to ensure the legality of its implementation. The regulations relating to waqf are contained in the Law of the Republic of Indonesia Number 41 of 2004; Government Regulation No. 42 of 2006 concerning the Implementation of Waqf; and Regulation of the Minister of Religion of the Republic of Indonesia No. 4 of 2009 concerning Administration of Cash Waqf Registration